The relation between education and economic growth for the period 1990 to 2020: A dynamic panel data model - Baya, Abdat; Abdelwahab, Boubaa; Touitou, Mohammed (International journal of economic perspectives, 2024)
This study aimed at examining the relationship between economic growth and education in 62 selected countries, in the period 1990–2020. To prove these relationships, we used average years of schooling as a proxy for human capital, as well as Arellano and Bond’s (1991) methodology. Our results are in favor of the theory according to which education is of vital importance to explain the growth rate of an economy. We found that the primary education level, out of the three used in the sample, significantly influences a country’s economic growth rate.